Satisfaction with online learning among MDAB students at UiTM Kelantan transition from high school to university / Siti Dalina Tumiran @ Kamal Nasser and Junaidah Hanim Ahmad - Tumiran @ Kamal Nasser, Siti Dalina; Ahmad, Junaidah Hanim (2021)
The purpose of this study is to examine the students' satisfaction towards online learning specifically the Mengubah Destini Anak Bangsa students at Universiti Teknologi MARA Cawangan Kelantan. Satisfaction is measured by the most satisfied online learning method, student satisfaction with online learning materials, and student satisfaction with student-lecturer engagement. This research is a case study that used a quantitative method. Only one particular group, Mengubah Destini Anak Bangsa students from only one Universiti Teknologi MARA (UiTM) branch campus, UiTM Cawangan Kelantan, were involved in this study. Research findings showed that pre-recorded video is the most satisfying online learning method, while clear and understandable guidelines and rubrics for each project is the most satisfying online learning material